THE TREND OF CONFLICT IN INDONESIA 2016 - Madjid, Adnan; Hidayat, Eri; Susilawati, Ningsih (PEOPLE: International Journal of Social Sciences, 2017)
Indonesia with various diversities is a country that has a high potential conflict. In general, the conflict in Indonesia is still not in spite of structural problems as a result of lack of uneven development and distribution of development outcomes. The inability of stakeholders and policy makers in managing conflicts are allegedly very likely to trigger large-scale social conflicts that have broad impact in a long time.Intensification of the conflict will be impact the development if the conflict resolution approaches that do less qualified or cannot extract the root of the real problem. The research approach used in this research is qualitative approach. Furthermore the type of research approach of this research is descriptive; the research seeks to do a current problem solving based on the data. The result showed that the vulnerable areas of conflict are DKI Jakarta and Papua province. Meanwhile, the provinces completely unrecorded have significant conflicts are Bali, Bangka Belitung, Banten, Bengkulu, Gorontalo, East Java, South Kalimantan, North Kalimantan, North Maluku, West Nusa Tenggara, West Papua, Central Sulawesi, North Sulawesi, West Sumatra and South Sumatra. In this case, Batam is a reflection of the rapid development of Indonesia with a good development condition which also increases the population growth. Based on the data obtained and the analysis conducted in this research, it is shown that there is a change of dynamic of conflict in Indonesia between this year and the previous years (compare to Map of Conflict 2014). In this case, DKI Jakarta still seems as a province with the highest number of conflict issues in Indonesia. On the other hand, it is recorded that Papua is still becoming an area with the most conflict issues thought the number is less than the previous year.